The potential of Citizen Science for mapping landscape change in Arctic permafrost regions - Fritz, Oliver; Marx, Sabrina; Herfort, Benjamin; Kaiser, Soraya; Langer, Moritz; Lenz, Josefine; Thiel, Christian; Zipf, Alexander (Herbert Wichmann Verlag, VDE VERLAG GMBH, Berlin/Offenbach, 2022)
Monitoring permafrost thaw in the Arctic is essential for assessing global climate change impact. Citizen science approaches can make a crucial contribution to this. In a case study using a micro-mapping methodology, visitors of an exhibition mapped polygonal soil patterns in satellite images of the Arctic. The evaluation of the collected data reveals that mapping such patterns poses a bigger challenge than more established task types, such as building detection. A simplification of the task using a binary detection approach increases the data quality of permafrost mapping. Citizen science shows great potential for permafrost research, although methods must be further tested.